(untitled) (Bangladesh Journal of Medical Science, 2016)
Introduction: Hepatoblastoma is a disease that has a variety of clinical manifestations. This fact complicates the diagnosis of a large number of cases of this disease. Case presentation: A 64-year-old female Ukrainian patient was admitted to the anesthesiology and reanimation department in critical condition with a diagnosis: dissecting abdominal aortic aneurysm. Despite to the complex of treatment and diagnostic measures after 10 hours was established a biological death. At autopsy of the patient were detected changes that characteristic for hepatoblastoma. Histological examination of the liver revealed the next diagnosis: poorly differentiated hepatocellular liver cancer. Conclusions: The patient had non-typical progress of the hepatoblastoma, which led to the erroneous diagnosis and incorrect chosen of the treatment strategy. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.292-296